Edukasi pada Penyalahguna Napza dalam Upaya Peningkatan Kualitas Hidup Penyalahguna Napza di Stakoetoe Medan Plus Padang Bulan - Martina, Siska Evi; Gultom, Rumondang; Sinaga, Janno; Hartoyo, Riska; Suniasih, Ni Wayan; Hia, Agustina; Halawa, Mirnasari; Zebua, Maria (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Narcotic, psychotropic, and addictive substance abuse (NAPZA) is a serious problem that affects the quality of life of many people at various levels of society.  Good quality of life is a state or state of life for an individual or group of people in a particular place and time in which they can experience positive emotions in the form of happiness and satisfaction.  One way to help drug addicts maintain a good quality of life is through rehabilitation programs. One of the rehabilitation facilities that plays an important role in this is Stacoetoe Medan Plus Rehabilitation. However, the success of this rehabilitation also depends on a holistic approach that includes educational aspects. General Goal: 4,444 drug addicts will be able to perform and optimize activities that will improve their quality of life and increase their productivity.  Specifically: Know the basic principles for improving quality of life (understanding, goals, characteristics of people who already have a good quality of life) and understand the supporting factors for improving quality of life and take steps to improve their quality of life.  Quality of life.  The method used is qualitative method.  Conducted at Stakoetoe Medan Plus, Jamin Pinting Street, and Pasar VII Street No. 45, Padang Bulan.  The number of participants in this consultation was 36 people.